Stunting dan Perkembangan Balita Usia 36-59 Bulan di Jakarta dan Papua - Desi Intan Sari; Indah Purnama Sari (Nutri-Sains: Jurnal Gizi, Pangan dan Aplikasinya, 2022)
This study aims to analyze the relationship between stunting and child development of aged 36-59 months in Jakarta and Papua. This study used secondary data from the 2018 Indonesia Basic Health Survey with a cross-sectional design. The target population was mothers who have toddlers aged 0-59 months in Indonesia. The sample was mothers who have toddlers aged 36-59 months in Jakarta and Papua (335 children in Jakarta and 453 children in Papua). Samples were selected using the multistage random sampling method. This study used the Chi Square Test on bivariate analysis and the Multiple Logistic Regression Test on multivariate analysis with an alpha of 5%. The results showed that there was no significant relationship between stunting and child development in Jakarta (p=0.468). Meanwhile, the results of a study in Papua showed that there was a relationship between stunting and the development of children aged 36-59 months (PR=3.078; 95% CI=1.619-5.852) after controlling for age, sex, mother's education, environmental sanitation, and infectious disease. The recommendations in this study were increasing access to environmental sanitation and health as an effort to prevent stunting and developmental delays in children.Â Penelitian ini bertujuan menganalisis hubungan antara stunting dan perkembangan anak usia 36-59 bulan di Jakarta dan Papua. Penelitian ini menggunakan data sekunder Riset Kesehatan Dasar (Riskesdas) 2018 dengan desain cross-sectional. Populasi target adalah ibu yang memiliki balita usia 0-59 bulan di Indonesia. Sampel adalah ibu yang memiliki balita usia 36-59 bulan di Jakarta dan Papua dengan jumlah 335 anak di Jakarta dan 453 anak di Papua. Pemilihan sampel dengan teknik multistage random sampling. Penelitian ini menggunakan Uji Chi-Square pada analisis bivariat dan Uji Regresi Logistik Ganda pada analisis multivariat dengan alpha 5%. Hasil penelitian menunjukkan tidak ada hubungan yang signifikan antara stunting dan perkembangan anak di Jakarta (p=0,468). Sementara itu, hasil penelitian di Papua menunjukkan bahwa terdapat hubungan antara stunting dan perkembangan anak usia 36-59 bulan (PR=3,078; 95% CI=1,619-5,852). Hal itu didapatkan setelah dikontrol oleh umur, jenis kelamin, pendidikan ibu, sanitasi lingkungan, dan penyakit infeksi. Rekomendasi dalam penelitian ini yakni peningkatan akses sanitasi lingkungan dan kesehatan sebagai upaya pencegahan stunting dan keterlambatan perkembangan pada anak.